2014
DOI: 10.1080/02626667.2014.907496
|View full text |Cite
|
Sign up to set email alerts
|

The unbearable fuzziness of being sustainable: an integrated, fuzzy logic-based aquifer health index

Abstract: We introduce a groundwater sustainability index offering a novel combination of features. It is holistic in the sense that it incorporates both water quantity and water quality indicators. The former employs the signalto-noise ratio of long-term trends estimated via robust regression; the latter uses concentration of the primary contaminant of concern. A fuzzy inference system integrates these unlike metrics. The system also explicitly encodes expert knowledge and stakeholder values, and directly acknowledges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…If Envision were used in conjunction with a groundwater specific sustainability index (such as [4,[10][11][12][13]), both the water system and the individual water project could be reviewed together in a truly holistic manner. A combination of both types of indices would provide the most integrated and thorough view of sustainability in groundwater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If Envision were used in conjunction with a groundwater specific sustainability index (such as [4,[10][11][12][13]), both the water system and the individual water project could be reviewed together in a truly holistic manner. A combination of both types of indices would provide the most integrated and thorough view of sustainability in groundwater.…”
Section: Discussionmentioning
confidence: 99%
“…Sandoval-Solis et al [9] have developed a water sustainability index based on management policies and mostly focus on technical aspects of sustainability; however, no environmental, social, or economic criteria are included [10]. In groundwater, different methods have been used to overcome the challenges associated with creating a water sustainability index and have included: analytic hierarchy processes in conjunction with information entropy theories [11], fuzzy logic [12], groundwater footprints [4], and an unweighted composite index [13].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the driven results from WQI and its developed fuzzy index, similar performance was observed in most of the cases. As Fleming et al (2014) explained, a major advantage of a fuzzy logic approach for constructing of environmental indices, relative to conventional approaches based on weighted averages, is that the rules of a fuzzy expert system can be built such that good quality in one parameter does not hide bad quality in another. In the present paper, in Table 7 the similar philosophy has been adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Article [8] presents the groundwater stability index, which offers a new combination of characteristics in which the signal-to-noise ratio of long-term trends is used, estimated using reliable regression and the Article [9] substantiates the methodology for assessing the impact of changes related to groundwater and climate change on the needs for basic and environmental runoff (EFN) and showed that under average meteorological conditions, the basic runoff in the main streams still meets the requirements of EFN. It also determined that anthropogenic changes have a significant impact: drainage caused a 25-40% reduction in base runoff, groundwater abstraction caused 5-28%, and climate change will potentially cause an additional 33-70% reduction by 2050.…”
Section: Introductionmentioning
confidence: 98%